2012
DOI: 10.4103/1319-2442.98164
|View full text |Cite
|
Sign up to set email alerts
|

Dural sinus thrombosis - A rare manifestation of internal jugular venous occlusion

Abstract: The dural sinus thrombosis is an uncommon complication of a commonly done procedure of central venous catheterisation. We present a case of massive hemorrhagic venous infarct with gross cerebral edema due to dural sinus thrombosis along with right internal jugular vein thrombus. A 21-year-old male patient presented to the emergency department with fever and swelling of the right neck four days following discharge after his prior hospitalization two weeks ago for acute renal failure due to severe gastroenteriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…We searched PubMed using the keywords (internal jugular vein AND catheter AND thrombophlebitis OR thrombosis) and excluded reports with no description of symptoms, treatment, or complications. We retrieved 12 relevant articles (Table 1) [10][11][12][13][14][15][16][17][18][19][20][21]. These articles included 14 patients with catheter-related IJV thrombosis, but only three cases of thrombophlebitis [10,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…We searched PubMed using the keywords (internal jugular vein AND catheter AND thrombophlebitis OR thrombosis) and excluded reports with no description of symptoms, treatment, or complications. We retrieved 12 relevant articles (Table 1) [10][11][12][13][14][15][16][17][18][19][20][21]. These articles included 14 patients with catheter-related IJV thrombosis, but only three cases of thrombophlebitis [10,11,13].…”
Section: Discussionmentioning
confidence: 99%
“…11 In case of septic emboli, right or left atrial thrombi, pulmonary embolism and dural sinus thrombosis, venous thrombosis may be a fatal condition. 12,13…”
Section: Discussionmentioning
confidence: 99%
“…11 In case of septic emboli, right or left atrial thrombi, pulmonary embolism and dural sinus thrombosis, venous thrombosis may be a fatal condition. 12,13 Jugular vein thrombosis can be diagnosed by ultrasonography, CT and MRI modalities. However, our patient underwent an MRI in order to exclude any possible bone and soft tissue infectious pathology.…”
Section: Discussionmentioning
confidence: 99%
“…12 A report of dural sinus thrombosis as a manifestation of IJV occlusion described how gross cerebral edema led to death in that patient. 13 Yu et al 14 reported on the role of cranial venous outflow abnormalities in the development of brain edema after ischemic events which results in further functional compromise. Pseudotumor cerebri following neck dissection has also been documented as a complication caused by venous outflow obstruction in cases where reconstruction of the IJV has not occurred.…”
Section: Morbidity Of Ijv Resectionmentioning
confidence: 99%